PAReTT: Python Automated Retrieval of TimeTree data - (:unkn) unknown (My University, 2023)
PAReTT is a menu-driven module used to interact with the Time Tree resource, specifically designed to automate batch retrieval of data for a list of species. Three main types of data can be retrieved using PAReTT: (1) Divergence times, between an individual pair or between all species in a list, (2) Evolutionary timelines, for individuals or a list species, and (3) Time trees of the divergence times, either for all available species within a specified taxon or between individual species supplied as a list. When working with a list of species, the best place to start is by using the first menu option to check the data availability of species in the list and removing any species for which data is not available.
Keywords: African Research